2006
DOI: 10.1152/ajpregu.00858.2005
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of dietary carbohydrates after prolonged effort modifies muscle sarcoplasmic reticulum responses in exercising males

Abstract: The hypothesis tested was that disturbances in the sarcoplasmic reticulum (SR) Ca2+-cycling responses to exercise would associate with muscle glycogen reserves. Ten untrained males [peak O2 consumption (VO2 peak) = 3.41 +/- 0.20 (SE) l/min] performed a standardized cycle test (approximately 70% VO2 peak) on two occasions, namely, following 4 days of a high (Hi CHO)- and 4 days of a low (Lo CHO)-carbohydrate diet. Both Hi CHO and Lo CHO were preceded by a session of prolonged exercise designed to deplete muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 50 publications
5
55
0
Order By: Relevance
“…Another study from the same group of researchers supported these observations by reporting a similar association following 4 days of low or high CHO diet in untrained women (9). Thus, there are convincing data demonstrating a direct association between SR vesicle Ca 2+ release rate and muscle glycogen content and these data gives further support to the existence of a critical threshold of glycogen required to protect SR Ca 2+ release as previously suggested by Duhamel and colleagues and Ørtenblad and colleagues (10,33). As SR Ca 2+ regulation is quantitatively, but not qualitatively, different between fiber types with an approximately 4 times higher SR uptake and -release rates in MHC II fibers (33).…”
Section: Figure 1 and 2 Near Heresupporting
confidence: 69%
See 3 more Smart Citations
“…Another study from the same group of researchers supported these observations by reporting a similar association following 4 days of low or high CHO diet in untrained women (9). Thus, there are convincing data demonstrating a direct association between SR vesicle Ca 2+ release rate and muscle glycogen content and these data gives further support to the existence of a critical threshold of glycogen required to protect SR Ca 2+ release as previously suggested by Duhamel and colleagues and Ørtenblad and colleagues (10,33). As SR Ca 2+ regulation is quantitatively, but not qualitatively, different between fiber types with an approximately 4 times higher SR uptake and -release rates in MHC II fibers (33).…”
Section: Figure 1 and 2 Near Heresupporting
confidence: 69%
“…Recent findings from human studies support the findings in animal models where Ca 2+ kinetics is influenced by glycogen levels (9,10,33). Duhamel and colleagues (10) examined the relation between muscle glycogen content and SR vesicle Ca 2+ release rate in untrained males during a prolonged fatiguing cycling session at ≈70 % of ̇O 2peak . The cycling session was preceded by a glycogen depleting exercise session and four days of either low or high carbohydrate (CHO) diet.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Many researchers have demonstrated that higher glycogen content in skeletal muscle before exercise results in improved performance in both prolonged endurance exercise and high-intensity intermittent exercise [2][3][4][5] . Recent in vitro studies also have shown that higher glycogen content before contraction is associated with the attenuation of force reduction during repeated tetanic contractions [6][7][8][9] . Therefore, during the post-exercise phase, glycogen repletion in skeletal muscle should be one of the most important factors for performance in the subsequent exercise.…”
Section: Introductionmentioning
confidence: 99%